The Effect of Interest Rates and Fluctuations in World Oil Prices on the Profitability of Islamic Banking in Qatar with Inflation as a Moderating Variable 2010-2024 - Kholidatul Mila; Meldona Meldona (Jurnal Maksipreneur, 2026)
This study analyzes how interest rates and fluctuations in world oil prices affect the profitability of Islamic banking in Qatar, with inflation as a moderating variable, over the period 2010–2024. Using a quantitative panel regression approach on data from four Islamic banks in Qatar, the results show that interest rates have a significant negative effect on profitability, while fluctuations in world oil prices have a significant positive effect on ROA. Inflation has a negative effect on profitability and moderates the relationships between interest rates and ROA and between world oil prices and ROA through quasi-moderation. Overall, all variables have a significant effect on profitability, confirming that global and domestic macroeconomic dynamics, especially changes in interest rates, oil prices, and inflation, play an important role in determining the stability and performance of Islamic banking in Qatar.